1987
DOI: 10.3164/jcbn.3.189
|View full text |Cite
|
Sign up to set email alerts
|

Ulcer Formation in Rat Stomach with Diethyldithiocarbamate

Abstract: SummaryIt has been suggested that superoxide radicals play an important role in the pathogenesis of gastric mucosal lesions after ischemia. To prove a participation of O-2 in gastric mucosal lesion formation, diethyldithiocarbamate (DDC), an inhibitor of Cu,Zn-superoxide dismutase (SOD), was injected into rats and its ulcerogenicity was examined. Subcutaneous injection of DDC was employed, because of high mortality after intraperitoneal injection of the drug. At 7 h after the injection of the drug, many ulcers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 19 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…5) . DDC is a powerful copper-chelating agent, an inhibitor of SOD, and a scavenger of O 2 d) (Ogino et al 1987). The decrease in DCF fluorescence after addition of DDC (Fig.…”
Section: C9 and C10 Hydrocarbon Solvents Elevate Respiratory Burst Inmentioning
confidence: 95%
“…5) . DDC is a powerful copper-chelating agent, an inhibitor of SOD, and a scavenger of O 2 d) (Ogino et al 1987). The decrease in DCF fluorescence after addition of DDC (Fig.…”
Section: C9 and C10 Hydrocarbon Solvents Elevate Respiratory Burst Inmentioning
confidence: 95%
“…Salim [36] found that radical removing agents such as dimethylsulfoxide and allopurinol, prevented the de velopment of chronic duodenal ulcers produced by intra venous reserpine. Ogino et al [37] reported that diethyldithiocarbamate, an inhibitor of CuZnSOD, was ulceragenic and that reactive oxygen species were involved in the pathogenesis of mucosal injury. It has, however, been an unsolved problem whether reactive oxygen species can cause gastric deep ulcer.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that DDC has many biological actions. With regard to the toxic effect of DDC, it has been reported to potentiate oxygen toxicity in brain (Puglia & Loeb 1984) and lung (Goldstein et al 1979).and to cause gastric ulcers (Ogino et al 1987;Ishiyama et al 1988). It has been suggested that these deleterious effects of DDC were due to an inhibition of cytosolic SOD activity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that DDC potentiates oxygen (Puglia & Loeb 1984) and xenobiotics toxicities (Goldstein et al 1979) and causes astrocyte cell toxicity (Trombetta et al 1988). We have reported previously that DDC caused gastric ulcers in rats (Ogino et al 1987;Ishiyama et al 1988). In the liver, it has been reported that long-term treatment with disulfiram, an oxidized form of DDC, caused hepatotoxicity in man (Keeffe & Smith 1974;Eisen & Ginsberg 1975;Ranek & Andeasen 1977) but there have been no such reports in experimental animals.…”
mentioning
confidence: 88%